(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract:Â the teacherÂ is an essential componentÂ in the process ofÂ teaching and learningÂ teachersÂ performanceÂ indicationÂ has not beenÂ fullestÂ due toÂ the role ofÂ kepemimpinÂ does not runÂ as expected.Â Based on the background of this research aim to know the influence of leadership, Self efficacy and performance against the Organization’s commitment to teacherstype ofÂ this researchÂ isÂ quantitative research,Â data collectionÂ MethodsÂ usedÂ in this researchÂ are:Â observation,Â questionnaires,Â review of the literature.Â populationÂ studiesÂ in junior highÂ CountryÂ 7Â ManadoÂ totaledÂ 63Â teachers.Â Methods ofÂ analysisÂ used wasÂ MultipleÂ LinearÂ Regression The results showed efficacy, self Leadership and organizational commitment is very influential on performance of existing teachers in JUNIOR HIGH SCHOOL the country 7 Manado. The value of the correlation coefficient r = 0.896 demonstrated that Leadership, self efficacy and organizational commitment have a very strong influence and significantly to the improved performance of teachers in JUNIOR HIGH SCHOOL In the country 7 Manado. The value of the coefficient of determination r Â² = 0.802 suggests that variations in Country JUNIOR HIGH SCHOOL Leadership 7 Manado 80.2% in influence by the magnitude of efficacy, self Leadership and organizational commitment, while the remaining 19.8% in the influence of other factors Â Keywords: Leadership, Self Efficacy, commitment and performance of teachers Organizations Â